STUDI HISTOLOGIK SEREBELUM CODOT (Rousettus sp.) DENGAN PEWARNAAN CRESYL ECHT VIOLET - , KARINA MAYANG SARI, Dr. drh. Tri Wahyu Pangestiningsih, MP ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Indonesia as the second megadiversity country, has diverse animals, one of them is fruit bats (Rousettus sp.). Fruit bats can eat and rest while hanging their hand on a tree branch with the head position below the body. This unique behavior need control of balancing by brain. Cerebellum is a part of the brain that regulates the body's balance. The aim of this study is examine the histologi of fruit batâs cerebellum and to complete the anatomy information of wildlife animals. This study is expected to provide information on the histologi of the cerebellum codot . Five fruit bats from Central Java as samples. Cerebellum processed in paraffin blocks and cut in 12 Î¼m thickness. Then, performed Cresyl echt Violet staining. The tissue section were observed using a microscope equipped with digital camera. Then analyzed using Optilab Image Raster, Microsoft office Excel, CorelDRAW X6 and Paint. The results show that fruit bats cortex cerebellar are divided in three layers such as molecular, piriform and granular layers. Neurons of molecular layer are stelat cells, located on the surface with a diameter 6.24 Â± 0.76 Î¼m and the density 17.07 Â± 3.8 cell/3000 Î¼m2, whereas basket cells located in the inner the diameter 5.83 Â± 0.77 Î¼m with density 8.4 Â± 1.05 cell/3000 Î¼m2. Piriformis layer composed of Purkinje cells, shaped like a pear, the diameter 15.6 Â± 1.72 Î¼m with density 26.3 Â± 5.9 cell/3000 Î¼m2. There are two kinds of neurons in granular layer such as small neurons, the diameter 2.76 Â± 0.35 Î¼m with density of 187 Â± 41.7 cells/3000 Î¼m2 and Golgi cells 5.29 Â± 0.69 Î¼m in diameter with density 5.9 Â± 1.4 sel/3000 Î¼m2. In the medulla of cerebellum, there are four pairs of nuclei, from lateral to medial are dentate, emboliform, globose and fastigii nuclei with cell diameters 14,71 Â± 1,57 Î¼m